Locked in and coming out a textual analysis of Filipino boys' love during the Covid-19 pandemic - Manangan, John Carlo C.
In 2020, Filipino audiences saw the rise of a new genre of Filipino-produced shows characterized by narratives of romance between two young boys — Filipino Boys' Love. Its popularity came during a time of unprecedented circumstances brought on by the COVID-19 pandemic that has imposed new restrictions and health protocols in the country, including new protocols in media productions.